Key Features to Inform Student Outcomes: Learning from a High School Healthcare Education Program. Issue 2 (April 2018) - Thessin, Rebecca A.; Scully-Russ, Ellen; Hildreth, Jeanine; Lieberman, Daina S.
At a time when U.S. policymakers are demonstrating their commitment to CTE established to address particular workforce shortage areas, this mixed methods evaluation study sought to understand the key features and outcomes of an existing healthcare education program (HEP) founded with this intent. Findings demonstrated that the HEP incorporates several unique features that should be considered by other programs including hands-on work using hospital equipment, workplace observations, and a strong emphasis on career decision-making efficacy. Evidence showed that students who continue in a Career and Technical Education (CTE) program for more than one year may exhibit somewhat higher rates of college enrollment.